2019
DOI: 10.1091/mbc.e19-02-0090
|View full text |Cite
|
Sign up to set email alerts
|

Constricted migration modulates stem cell differentiation

Abstract: Tissue regeneration at an injured site depends on proliferation, migration, and differentiation of resident stem or progenitor cells, but solid tissues are often sufficiently dense and constricting that nuclei are highly stressed by migration. In this study, constricted migration of myoblastic cell types and mesenchymal stem cells (MSCs) increases nuclear rupture, increases DNA damage, and modulates differentiation. Fewer myoblasts fuse into regenerating muscle in vivo after constricted migration in vitro, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 67 publications
2
23
2
Order By: Relevance
“…In contrast to previous reports (Moriarty and Stroka, 2018;Pfeifer et al, 2018;Smith et al, 2019;Xia et al, 2019), we did not find evidence of increased cell cycle arrest during confined migration.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous reports (Moriarty and Stroka, 2018;Pfeifer et al, 2018;Smith et al, 2019;Xia et al, 2019), we did not find evidence of increased cell cycle arrest during confined migration.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be due to differences in the experimental systems used in the various studies: previous experiments used either transwell plates (Pfeifer et al, 2018;Smith et al, 2019;Xia et al, 2019) or long microfluidic channels (Moriarty and Stroka, 2018) and assessed cell cycle progression after 12-24 hours of confined migration. In contrast, in our microfluidic devices, only parts of the cell are within the tight constriction at a given time, similar to the situation of cells migrating in collagen matrices (Wolf et al, 2013), and we evaluated cell cycle stage while the cell was moving during the constriction, which typically occurred within 1-3 hours (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing to the uncertainty about the molecular mechanism responsible for the confined migration-induced DNA damage is that previous studies have provided at times conflicting results on the association between DNA damage and NE rupture. Although some studies reported that DNA damage requires NE rupture, [13][14][15]26,27 others found that DNA damage can occur in the absence of NE rupture as cells squeeze their nuclei through tight spaces. 10,28 Using time-lapse microscopy and a broad panel of cell lines co-expressing fluorescent reporters for DNA damage and NE rupture, we found that, in some cell lines, mechanical deformation of the nucleus is sufficient to cause DNA damage, although in other cell lines, DNA damage is primarily associated with NE rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The results resonate with findings reported in this issue for interphase stem cells migrating through small pores. Lucas Smith and coworkers propose such a model for what can happen as a stem cell migrates through dense matrix to a site of injury prior to differentiation and tissue regeneration. Nuclear envelope rupture leads to loss of transcription factors and DNA repair factors, which associates with increased DNA damage and suppressed cell cycle, but rupture can be rescued by inhibiting actomyosin, which slows migration.…”
mentioning
confidence: 99%